Exploring the New Perspectives of Doping in Sports - Shweta Sharma; Sonia Joshi; Aditi Dubey (Indian Journal of Forensic Medicine and Pathology, 2025)
Doping is appearing as one of the major problems in the world. It can be a serious problem in the world, it can be de𿿿ned based on various perspectives. Dopingisrelated to abuse of drugs in sports. Doping along with performance enhancing substances is a current problem being dealt internationally. WADA (World AntiDoping Agency) has banned doping. Although, it is almost universally present among athletes aiming to win without any proper efforts in the right direction. Among the cases of doping reported it becomes dif𿿿cult for identifyingthe intent if present behind it. Besides, lack of awareness on the ill effects of doping on the health also continues to be an ignored issue. There are some athletes who feel incapable of achieving needed natural abilities including speed, strength and stamina unless intake of illicit substances are done. In some cases, the evidences were not contested and athletes admitted the use of illicit substances. However, in other cases, athletes refused the use of doping to enhance performance and claimed to have involuntarily or passively absorbed the drug. The purpose of this review is to evaluate the in and outs of doping which includes its adverse effects, causes, etc. Previous studies on this topic discussed many cases, on which it was revealed that diagnosis of doping can take too much time or less (hours or days) depending upon the type of doping. After doping several signs and symptoms can be seen; such as high blood pressure, acne on oily skin, aggressive behavior, insomnia, agitation, dizziness, headache etc. Articles referenced in this review were of great help in understanding various aspects of doping.